VULNERABLE GROUPS IN ALBANIA AND THEIR PROTECTION - Gjergji, Elda (European Scientific Journal, ESJ, 2012)
In early 1990s, Albania begins to make political and economic reforms toward democracy. Among others, reforms to improve the economy and to protect the rights of its citizens were of the immediate need, and they started to show improvements in Albanian society. However, the economic and social reforms in Albania are accompanied with an increase in the number of people who are considered at risk or outside the mainstream of the society. The treatment of social protection issues for vulnerable groups in Albania has not been systematically examined despite their vital importance to poverty reduction. In recent years, international development discourse has started to recognize more fully the importance of adequate social protection. There is no guarantee that social protection and equity issues will come higher up the agenda of the democratization of Albania, not least because the international institutional context in which they are being developed which historically has not prioritized social protection. While civil society involvement has varied substantially, civil actors are often some of the strongest advocates of inclusive and equitable development policies, including adequate social protection in Albania. At the end, this paper is primarily based on documents of state institutions and international organisms working in Albania.